The Emerald handbook of women and entrepreneurship in developing economies - Rezaei, Shahamak; Li, Jizhen; Ashourizadeh, Shayegheh; Ramadani, Veland; Gërguri-Rashiti, Shqipe, 1979- (Emerald Publishing, 2021)
The Emerald Handbook of Women and Entrepreneurship in Developing Economiesexamines women's role in entrepreneurial practices in a range of developing countries and applies unique strategic contextual frameworks to analyse, interpret and understand individual processes, themes and issues.